More Time is Better : An Evaluation of the Full-time School Program in Uruguay - Cerdan-Infantes, Pedro; Vermeersch, Christel (World Bank, Washington, DC, 2012)
This paper estimates the impact of the full-time school program in Uruguay on standardized test scores of 6th grade students. The program lengthened the school day from a half day to a full day, and provided additional inputs to schools to make this possible, such as additional teachers and construction of classrooms. The program was not randomly placed, but targeted poor urban schools. Using propensity score matching, the authors construct a comparable group of schools, and show that students in very disadvantaged schools improved in their test scores by 0.07 of a standard deviation per year of participation in the full-time program in mathematics, and 0.04 in language. While the program is expensive, it may, if well targeted, help address inequalities in education in Uruguay, at an increase in cost per student not larger than the current deficit in spending between Uruguay and the rest of the region.